2021
DOI: 10.3390/su13063103
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendments Boost Soil Fertility and Rice Productivity and Reduce Methane Emissions from Paddy Fields under Sub-Tropical Conditions

Abstract: Deteriorating soil fertility and gradually decreasing rice productivity along with higher greenhouse gas emissions from paddy fields have emerged as serious threats to the sustainability of rice production and food security. Rice production in the subtropical environment in Bangladesh is mostly dependent on synthetic inorganic fertilizer to maintain productivity; however, the inorganic fertilizer has negative effects on global warming. Climate-smart and resilient agricultural production systems are major conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…It is being grown in all habitable continents of the world, owing to its wide adaptability to a wide range of pedo-climatic conditions [4,5]. In Asia, it is cultivated with irrigation systems, while in Pakistan, rice is ranked the third most prominent crop, covering 10% of the cultivated area and contributing 17% to the total cereal production [6][7][8]. However, rice cultivation through nursery transplanting in a puddled field is cumbersome, time-consuming and is a prodigal water use method [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is being grown in all habitable continents of the world, owing to its wide adaptability to a wide range of pedo-climatic conditions [4,5]. In Asia, it is cultivated with irrigation systems, while in Pakistan, rice is ranked the third most prominent crop, covering 10% of the cultivated area and contributing 17% to the total cereal production [6][7][8]. However, rice cultivation through nursery transplanting in a puddled field is cumbersome, time-consuming and is a prodigal water use method [9].…”
Section: Introductionmentioning
confidence: 99%
“…The DSR offers several advantages, including faster plant growth, avoidance of transplanting shock, ease in cultivation, less labor and water requirements as well as early maturity [13][14][15][16][17]. Additionally, a significant reduction in methane emission was also accomplished with DSR [6]. However, weed infestation has remained the prime biological constraint limiting the productivity of DSR by up to 75-80% [14,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al [47] suggested the use of organic manure and chemical fertilizers enhanced grain output considerably. Organic manure and chemical fertilizers boosted rice straw yields [48]. These assumptions are supported by [40,49].…”
Section: Discussionmentioning
confidence: 84%
“…In investigation of forage barley intercropping with legumes, Strydhorst et al [26] revealed that intercropping with legumes crops produced higher protein than barley monoculture. The previous literature recommended that with the increase in the nutritional components in soil, the nutrition of crops is also increased but up to a certain rate [27,28]. Wheat and beans intercropping showed the highest photosynthetically active radiation (PAR) efficiency over their monoculture [29].…”
Section: Hay Vs Silagementioning
confidence: 99%